Innovations in Practice: MICHI, a brief cognitive‐behavioural group therapy for adolescents with depression – a pilot study of feasibility in an inpatient setting. Issue 4 (21st July 2012) - Straub, Joana; Koelch, Michael; Fegert, Joerg; Plener, Paul; Gonzalez‐Aracil, Inma; Voit, Anja; Sproeber, Nina
<x xml:space="preserve">Abstract</x> Background Group therapy is an economic intervention, allowing for fast access, for the treatment of several depressed adolescents simultaneously; evaluated manualised programs, however, are scarce. Method Nine depressive adolescent inpatients (M = 16.33 years; SD = 1.92) participated between October 2009 and March 2010 in a brief manualised group therapy programme (MICHI), which was evaluated with respect to feasibility and trends of efficacy. Results MICHI demonstrated good feasibility, was positively evaluated by the participants by means of an evaluation questionnaire ranging from 1 (very bad) to 10 (very good) (M = 7.22; SD = 1.79), and showed significant reduction of depressive symptoms (z = −2.66, p = .008) assessed by means of a clinical interview. Conclusions Feasibility of MICHI was demonstrated and larger trials for efficacy will follow.